Effect of longevity spinach leaves powder (LSP) as a broiler feed additive on some physical and chemical parameters of frozen stored thigh meat - Zaid Khidhir; Arazu Hamma; Mohammed Mohammed; Ayad Mahmood; Ahmed Al-Obaidi; Ziyad Aldoori (Mesopotamia Journal of Agriculture)
This investigation aimed to ascertain the impact of various concentrations of Longevity Spinach leaf powder (LSP) as broiler feed additives on chemical composition, some physical traits (each pH, Water holding capacity, and Cooking loss), Chemical and oxidative traits (Thiobarbituric acid, Free fatty acids, Total volatile nitrogen, Myaglobin and Met-Myoglobin) and validity period of the thigh meat which preserved for different freezing periods. 90 broiler chickens at the age of one day- (Ross-308) were distributed into six treatments randomly. A commercial concentrated diet was provided for all treatments. As a control, the T1 whithout additives. T2: 0.75 kg LSP per ton of feed; T3: 1.5 kg LSP per ton of feed; and T4: 2.25 kg LSP per ton of feed; T5: 3 kg LSP per ton of feed while T6 offers 3.75 kg of LSP per feed ton. After 35 days of Rearing, 6 broilers were randomly slaughtered for each treatment. Carcasses were washed with cooled water and dried with gauze then kept at refrigeration for 8 hrs. Carcasses thigh cut were placed in polyethylene bags then stored for 0, 30, and 90 days at -18 ℃ and required measurements were collected at each period's end. Results indicated that LSP treatments, especially T5 (adding 3 kg LSP / ton of feed), had a positive effect on all studied traits for most storage periods, and suggested that using LSP powder as natural additives to broiler feed enhances the quality attributes of meat and prolongs Its validity period in freezer Storage